Role of entropy in the ground state formation of frustrated systems - Sereni, J.G.; Sereni, Julián (Elsevier, 2018)
Fil: Sereni, J. G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina